Role of ghrelin in promoting catch-up growth and maintaining metabolic homeostasis in small-for-gestational-age infants - Zhang, Li; Liu, Jingfei; Gao, Dianyong; Li, Dong (Frontiers in Pediatrics, 2024)
Small-for-gestational age (SGA) has been a great concern in the perinatal period as it leads to adverse perinatal outcomes and increased neonatal morbidity and mortality, has an impact on long-term health outcomes, and increases the risk of metabolic disorders, cardiovascular, and endocrine diseases in adulthood. As an endogenous ligand of the growth hormone secretagotor (GHS-R), ghrelin may play an important role in regulating growth and energy metabolic homeostasis from fetal to adult life. We reviewed the role of ghrelin in catch-up growth and energy metabolism of SGA in recent years. In addition to promoting SGA catch-up growth, ghrelin may also participate in SGA energy metabolism and maintain metabolic homeostasis. The causes of small gestational age infants are very complex and may be related to a variety of metabolic pathway disorders. The related signaling pathways regulated by ghrelin may help to identify high-risk groups of SGA metabolic disorders and formulate targeted interventions to prevent the occurrence of adult dwarfism, insulin resistance-related metabolic syndrome and other diseases.